Business Plan The Development and Operation of Biomass Power Plant - Doležal, Tomáš; Lukeš, Martin, 1976-; Žádník, Josef; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The goals of this thesis are to create a comprehensive business plan manual from various business plan frameworks and to clarify project documentation necessary for the commencement of the biomass power plant. The theoretical part serves to the reader as a manual, how to write a business plan. In each section the thesis lists necessary questions to be answered, the theory and the recommendations what to include in the business plan. The practical part represents a complete business plan of the development and op-eration of the biomass power plant with focus on the political analysis, key resources and financial analysis. In the end of the thesis the investment decision criteria are pre-sented together with the risks analysis, providing a solid information base upon which a potential investor can decide, whether to invest into the project.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses